Uncertainty in the Management of Tropical Peatlands for Oil Palm Plantations due to Drainage Practices - Aswandi Aswandi (Universitas Andalas, 2023)
The conversion of tropical peatlands to oil palm plantations has affected the long-term storage stability of water and carbon. The conversion requires a drainage system that results in land subsidence and, in turn, reduces the carrying capacity of water storage and carbon stocks. This study aims to analyze subsidence from long-term observations (2004-2020) to obtain an appropriate water management measure for three scenarios of drainage depths at the oil palm plantations in Jambi Province. It is found that the reduction is quite variable depending on the level of drainage depths. The subsidence was 55 cm, 49 cm, and 34.7 cm for deep, moderate, and shallow drainage conditions. The groundwater level was deeper than 100 cm, which is far below the threshold of 40 cm, as stated in the government regulations. However, the regulations are still debated since subsidence must occur in drained peatlands regardless of the water level. The observed large subsidence implies that better water management in a new site is crucial and necessary to reduce the impact of peatlands degradation relative to current conditions and that high rates of land subsidence should be accepted as an inevitable change from the conversion of tropical peatlands to oil palm plantations.